Recent strategies for enhancing the therapeutic efficacy of stem cells in wound healing - Yongqing Zhao (BMC, 2021)
Abstract Skin wound healing is a multi-stage process that depends on the coordination of multiple cells and mediators. Chronic or non-healing wounds resulting from the dysregulation of this process represent a challenge for the healthcare system. For skin wound management, there are various approaches to tissue recovery. For decades, stem cell therapy has made outstanding achievements in wound regeneration. Three major types of stem cells, including embryonic stem cells, adult stem cells, and induced pluripotent stem cells, have been explored intensely. Mostly, mesenchymal stem cells are thought to be an extensive cell type for tissue repair. However, the limited cell efficacy and the underutilized therapeutic potential remain to be addressed. Exploring novel and advanced treatments to enhance stem cell efficacy is an urgent need. Diverse strategies are applied to maintain cell survival and increase cell functionality. In this study, we outline current approaches aiming to improve the beneficial outcomes of cell therapy to better grasp clinical cell transformation.